Development and characterization of spray-dried buko-milk shake powder. - Magalonga, Rayah Mae Febrero
Three ratios of the buko-milk shake were subjected to a rank for preference test. The ratios differed in the amount of coconut water with meat mixed with carabao?s milk, namely, 1:1, 2:1 and 3:1 designated as F1, F2 and F3, respectively. The F2 (2:1) ratio was established to be the most preferred ratio, F2 consistently garnered the highest rank in all 3 trials. F2 had a pH value of 6.11, Total soluble solids (TSS) of 8°Brix and titratable acidity (TA) of 0.1215% F2 ratio was used as basis for the slurry in spray drying to produce the buko-milk shake powder. Based on Attribute Rating Test, buko-milk shake powder from F2 ratio had a yellowish-white color, rough texture, weak coconut water odor and a strong carabao?s milk odor. It had 4.05% moisture content, 0.17% fat, 0% crude fiber, 4.54% protein, 2.35% ash, and 88.74% carbohydrates. It had an aw of (0.402), ph of 6.08 and TA of (0.096%). The buko-milk shake powder was reconstituted in varying water concentrations; 100%, 110% and 120%, designated as R1, R2 and R3, respectively. The ratios were subjected to a rank for preference test. R3 ratio garnered the highest rank and was established to be the most preferred ratio. Furthermore, out of 50 respondents, 86% liked the product.